1999
DOI: 10.1021/jp9841135
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Valence States of Transition-Metal Elements Using Energy-Filtered Transmission Electron Microscopy

Abstract: The properties of transition-metal oxides are related to the presence of elements with mixed valences, such as Mn and Co. Spatial mapping of the valence-state distribution of transition-metal elements is a challenge to existing microscopy techniques. In this letter, using the valence-state information provided by the white lines observed in electron energy-loss spectroscopy in a transmission electron microscope (TEM), an experimental approach is demonstrated to map the valence-state distributions of Mn and Co … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…Because of the short acquisition times, the requirement of high specimen stability that is a prerequisite for X-ray maps, acquired over minutes or hours, is less important with EFTEM imaging. Second, just as EELS can probe the local electronic structure of specimens, energy-selected images showing variations in local electronic structure can be formed (Batson et al 1994;Kimoto et al 1999;Wang et al 1999). Third, quantitative chemical images with spatial resolution of 1 nm and sensitivity for some elements at the ~1% level are possible (Elbert et al 2001).…”
Section: Energy-filtered (Ef) Imagingmentioning
confidence: 99%
“…Because of the short acquisition times, the requirement of high specimen stability that is a prerequisite for X-ray maps, acquired over minutes or hours, is less important with EFTEM imaging. Second, just as EELS can probe the local electronic structure of specimens, energy-selected images showing variations in local electronic structure can be formed (Batson et al 1994;Kimoto et al 1999;Wang et al 1999). Third, quantitative chemical images with spatial resolution of 1 nm and sensitivity for some elements at the ~1% level are possible (Elbert et al 2001).…”
Section: Energy-filtered (Ef) Imagingmentioning
confidence: 99%
“…[59][60][61][62]). Further, it has been demonstrated that of Cr(VI) make it a particular environmental concern, electron energy-fitered TEM imaging can produce valence Geochemical and microbiological processes of Cr specific maps of metals [63][64][65]. Determination of oxidation oxidation/reduction can drive both precipitation-dissolustate by EELS (as well as XPS and XAS) is accomplished by tion and ion absorption-desorption reactions in the analyzing valence-induced differences in the fine structure of environment.…”
Section: Introductionmentioning
confidence: 99%
“…In the EELS core-loss spectrum, the integral intensity ratio of the L 3 (2p 3/2 → 3d) and L 2 (2P 1/2 → 3d) excitation peaks is sensitive to the change in the valence states of transition metal cations [132][133][134][135]. Therefore, the oxidation states of transition metal cations can be identified by measuring the integrated intensities of L 2,3 edges.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%